2017
DOI: 10.1002/chem.201702694
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Induced Cadmium(II) Metal‐Organic Frameworks with Adjustable Guest‐Evacuated Porosity: Application in the Controllable Assembly of MOF‐Derived Porous Carbon Materials for Supercapacitors

Abstract: In this work, five new cadmium metal-organic frameworks (Cd-MOFs 1-5) have been synthesized from solvothermal reactions of Cd(NO ) ⋅4 H O with isophthalic acid and 1,4-bis(imidazol-1-yl)-benzene under different solvent systems of CH OH, C H OH, (CH ) CHOH, DMF, and N-methyl-2-pyrrolidone (NMP), respectively. Cd-MOF 1 shows a 3D diamondoid framework with 1D rhombic and hexagonal channels, and the porosity is 12.9 %. Cd-MOF 2 exhibits a 2D (4,4) layer with a 1D parallelogram channel and porosity of 23.6 %. Cd-MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 86 publications
0
24
0
Order By: Relevance
“…They also investigated the role of different solvents for Cd-MOF carbon precursors in the preparation of MOF-derived PCs [74]. Five different solvents (methanol, ethanol, isopropanol, DMF, NMP = N-methyl-2-pyrrolidone) were used to synthesize a series of new Cd-MOFs under the same mixed ligand system (bib and H 2 ipa = isophthalic acid).…”
Section: Cd-mof-derived Carbonsmentioning
confidence: 99%
“…They also investigated the role of different solvents for Cd-MOF carbon precursors in the preparation of MOF-derived PCs [74]. Five different solvents (methanol, ethanol, isopropanol, DMF, NMP = N-methyl-2-pyrrolidone) were used to synthesize a series of new Cd-MOFs under the same mixed ligand system (bib and H 2 ipa = isophthalic acid).…”
Section: Cd-mof-derived Carbonsmentioning
confidence: 99%
“…We previously found that the capacitance of MOF-derived carbon is closely related to many factors from the MOF precursors,s uch as the organic ligand, solvent, and topological structure. [22][23][24] As the central node of the MOFs, the metal ion undoubtedly plays an important role in the capacitance of MOF-derived carbon, and deservesb es ystematically researched.…”
Section: Syntheses Of Considerationmentioning
confidence: 99%
“…The series of isomorphous MOFs have been previously reported and synthesized by solvothermal reactions. [23,24] According to these reported methods, plenty of impurities will appear in the Teflonlined autoclave. In this work, we planned to use the series of MOFs as precursors to prepare MOF-derived carbon, so it is very important to collect al arge amount of pure MOF raw materials.…”
Section: Syntheses Of Mofsmentioning
confidence: 99%
“…To investigate this aspect, in our recent research, five new Cd-MOFsw ere prepared by solvothermalr eactions of Cd II ion with isophthalic acid and bib ligand under different solvent systemso fC H 3 OH, C 2 H 5 OH, (CH 3 ) 2 CHOH,D MF and N-methyl-2pyrrolidone( NMP), respectively ( Figure 6). [40] The solventn ot only behaves as the structure-directing agent for the self-assembly of Cd-MOFs, but also induces the different guest-evacuated porosity of MOFs,w hich was facilitated to perform as ystematical study on the effect of solvent. The porosity of MOFs could be employed as the template to produce the pore of carbon materials.T he resultss how that the specific surface area of MOF-derived carboni sc onsistent with the porosity of Cd-MOFs, and the latter is adjusted by the solvent.…”
Section: Solventsmentioning
confidence: 99%
“…The effect of solvent on the porosity of Cd-MOFs and specifics urface area of correspondingMOF-derived carbon. Reproducedw ith permission from reference [40]. Copyright 2017,Wiley-VCH. respectively.M oreover,t he addition of CTAB together with tris(hydroxymethyl)aminomethane( TRIS) brings about ac ooperative effect, which modulates the final morphology of ZIF-8 from cubic to octahedral, hexapods, burr puzzles and flowerlike shapes as the amount of TRIS increases.…”
Section: Additivesmentioning
confidence: 99%